2021
DOI: 10.1016/j.celrep.2021.109662
|View full text |Cite
|
Sign up to set email alerts
|

SCIMP is a spatiotemporal transmembrane scaffold for Erk1/2 to direct pro-inflammatory signaling in TLR-activated macrophages

Abstract: Immune cells are armed with Toll-like receptors (TLRs) for sensing and responding to pathogens and other danger cues. The role of extracellular-signal-regulated kinases 1/2 (Erk1/2) in TLR signaling remains enigmatic, with both pro-and anti-inflammatory functions described. We reveal here that the immune-specific transmembrane adaptor SCIMP is a direct scaffold for Erk1/2 in TLR pathways, with high-resolution, live-cell imaging revealing that SCIMP guides the spatial and temporal recruitment of Erk2 to membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 79 publications
(116 reference statements)
2
14
0
Order By: Relevance
“…Lastly, we examined LPS-induced cytokine responses in SCIMP-deficient BMMs and Syk-inhibitor treated BMMs. Consistent with our previous results ( 25 ), we found that the expression of proinflammatory cytokines TNF, IL-6, and IL-12p40 was significantly decreased in SCIMP-deficient BMMs in response to LPS compared with control BMMs ( Fig. 6 A ).…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Lastly, we examined LPS-induced cytokine responses in SCIMP-deficient BMMs and Syk-inhibitor treated BMMs. Consistent with our previous results ( 25 ), we found that the expression of proinflammatory cytokines TNF, IL-6, and IL-12p40 was significantly decreased in SCIMP-deficient BMMs in response to LPS compared with control BMMs ( Fig. 6 A ).…”
Section: Resultssupporting
confidence: 93%
“…3 C ). In addition, the recruitment of the SCIMP effector Erk1/2 ( 25 ) was not affected by Syk inhibition, suggesting the phosphorylation of SCIMP is not required for Erk1/2 binding ( Fig. S5 ).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations